Silicon nanowires - A versatile technology platform - Mikolajick, Thomas; Heinzig, Andre; Trommer, Jens; Pregl, Sebastian; Grube, Matthias; Cuniberti, Gianaurelio (Giovanni); Weber, Walter M. (Physica Status Solidi-Rapid Research Letters, 2013)
Silicon nanowires offer unique properties like inherent small diameters, quasi-one-dimensional current transport and the flexibility to combine materials that cannot be combined in bulk or thin film structures. Based on these properties electron devices, sensors as well as solar cells and lithium batteries can be envisioned that significantly outperform their thin film or bulk counterparts. The possibility to form silicon nanowires in a top-down process using bulk silicon or silicon-on-insulator substrates, gives this technology the potential for a seamless integration into integrated electronic systems. This Review gives an overview of important device applications of silicon nanowires. Starting with nanowire fabrication, the different device concepts will be introduced and their most important features are reported. Illustration of silicon nanowire formation and application in a reconfigurable device. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Li-ion batteries; Reconfigurable field effect transistors (RFET); Sensors; Silicon nanowires